2017
DOI: 10.2134/agronj2016.08.0464
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Volatilization from Urea Treated with NBPT and Two Nitrification Inhibitors

Abstract: Core Ideas A comparison of ammonia volatilization from granular urea treated with two commercially available nitrification inhibitors and the interaction with the urease inhibitor, NBPT. Nitrification inhibitors increased ammonia volatilization from surface‐applied granular urea compared to untreated urea. When treating urea with nitrification inhibitors, a urease inhibitor should be applied to reduce ammonia volatilization losses. Soil type specific recommendations may be needed when applying nitrification/ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Grain yield for the nitrification inhibitors was ranked pronitridine at 9.4 L ha -1 (9.02 Mg ha -1 ) = pronitridine at 18.7 L ha -1 (9.01 Mg ha -1 ) = non-treated (8.94 Mg ha -1 ) ≥ nitrapyrin (8.63 Mg ha -1 ). Differences between pronitridine and nitrapyrin might be due to differences in the longevity of these products in the soil or the ability to affect ammonia volatilization (Fox & Bandel, 1989;Aita et al, 2014;Frame, 2017). Yield data indicate that adequate N was supplied to the crop for high yields at 202 kg N ha -1 or greater, and no advantage was observed when adding a nitrification inhibitor when compared to the nontreated control.…”
Section: Uan At 202 Kg N Ha -1mentioning
confidence: 99%
See 1 more Smart Citation
“…Grain yield for the nitrification inhibitors was ranked pronitridine at 9.4 L ha -1 (9.02 Mg ha -1 ) = pronitridine at 18.7 L ha -1 (9.01 Mg ha -1 ) = non-treated (8.94 Mg ha -1 ) ≥ nitrapyrin (8.63 Mg ha -1 ). Differences between pronitridine and nitrapyrin might be due to differences in the longevity of these products in the soil or the ability to affect ammonia volatilization (Fox & Bandel, 1989;Aita et al, 2014;Frame, 2017). Yield data indicate that adequate N was supplied to the crop for high yields at 202 kg N ha -1 or greater, and no advantage was observed when adding a nitrification inhibitor when compared to the nontreated control.…”
Section: Uan At 202 Kg N Ha -1mentioning
confidence: 99%
“…Nitrification inhibitors have been utilized not only to reduce gaseous and leaching loss of N fertilizer by delaying nitrification of N fertilizers in the soil (Bremner & Blackmer, 1979;Aulakh et al, 1984;Bronson et al, 1992;Delgado & Mosier, 1996;Weiske et al, 2001;O'Callaghan et al, 2010;Khalil, 2011;Omode & Vyn, 2013;Aita et al, 2014;Fisk et al, 2015;Frame, 2017), but also to increase crop yields (Randall et al, 2003;Ruser & Schulz, 2015;Ren et al, 2017). The most consistent results in the north central U.S. with nitrapyrin (2-chloro-6-(trichloromethyl) pyridine) and dicyandiamide (DCD) were reported on coarse-textured soils with reduced rates of N (Malzer et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes urease and nitrification inhibitors are jointly added to urea fertilizer to decrease leaching and volatilization losses, but some recent studies have shown that nitrification inhibitors increase NH 3 losses by maintaining high soil pH due to urea hydrolysis, thus reducing the benefit of the urease inhibitor (Frame, 2017;Kim et al, 2012). In a study under controlled conditions, the mixture of both inhibitors caused the NH 3 losses to be like that of the nontreated urea (Soares et al, 2012).…”
Section: N Losses Through Leaching Nitrous Oxide Emission and Ammonmentioning
confidence: 99%
“…Extensive research has been conducted on NI's with several reviews on the effects of NI's on the reduction of N loss and the impact on crop production (Aulakh, Rennie, & Paul, 1984;Burzaco, Ciampitti, & Vyn, 2014;Cerrato & Blackmer, 1990;Cook et al, 2015;Fisk, Maccarone, Barton, & Murphy, 2015;Frame, 2017;Prasad, 1995;Wolt, 2004). Research on NI's has shown positive, neutral, or negative effects on grain yield (Quemada, Baranski, Nobel-de Lange, Vallejo, & Cooper, 2013;Wolt, 2004).…”
Section: Introductionmentioning
confidence: 99%